Take your mama to work today - Reichert, Amy (Atheneum Books for Young Readers, 2012)
Violet is very helpful when she visits her mother's office, and gives pointers on delivering the mail (be sure to decorate it with extra stamps and stickers), helping the boss with his big presentation (like a show-and-tell for grown-ups), and making business cards (after clearing the paper jam in the copier).